Measurement of IgE to hazelnut allergen components cannot replace hazelnut challenge in Dutch adults. Issue 5 (16th November 2021) - Lyons, Sarah A.; Welsing, Paco M. J.; Hakobyan, Mariam; Kansen, Hannah M.; Knol, Edward F.; Otten, Henny G.; van Ree, Ronald; Knulst, André C.; Le, Thuy‐My
Abstract: Background: Component‐resolved diagnostics (CRD) help predict hazelnut allergy (HA) in children, but are of unknown diagnostic value in adults. This study aimed to evaluate the diagnostic accuracy of IgE to hazelnut extract and components in adults. Methods: A Dutch population of consecutively presenting adults suspected of HA, who underwent a double‐blind placebo‐controlled food challenge, were included. Serum IgE to hazelnut extract and Cor a 1, 8, 9, and 14 was measured on ImmunoCAP. Diagnostic accuracy was assessed by area under the curve (AUC) analysis. Results: Of 89 patients undergoing challenge, 46 had challenge‐confirmed HA: 17 based on objective and 29 based on subjective symptoms. At commonly applied cutoffs 0.1 and 0.35 kUA /L, high sensitivity was observed for IgE to hazelnut extract and Cor a 1 (range 85–91%), and high specificity for IgE to Cor a 8, 9 and 14 (range 77–95%). However, the AUCs for hazelnut extract and components were too low for accurate prediction of HA (range 0.50–0.56). Combining hazelnut extract and component IgE measurements did not significantly improve accuracy. Higher IgE levels to Cor a 9 and 14 were tentatively associated with HA with objective symptoms, but the corresponding AUCs still only reached 0.68 and 0.63, respectively. Conclusions: Although hazelnut allergic adults are generally sensitized to hazelnut extract and Cor a 1, and hazelnut tolerant adults are usually not sensitized to Cor a 8, 9, or 14, challenge testing is still needed to accurately discriminate between presence and absence of HA in adults from a birch‐endemic country. Abstract : Dutch hazelnut allergic adults are usually sensitized to hazelnut extract and Cor a 1 (sensitivity 85‐91%). Dutch hazelnut tolerant adults are usually not sensitized to Cor a 8, 9, or 14 (specificity 77‐95%). Measurement of IgE to hazelnut allergen components (AUC 50‐56%) cannot replace hazelnut challenge for diagnosis of hazelnut allergy in adults in birch‐endemic regions.Abbreviations: AUC, area under the curve; DBPCFC, double‐blind placebo‐controlled food challenge; HN, hazelnut.